Maggots, Mucous and Monkey Meat: Does Disgust Sensitivity Affect Case Mix Seen During Residency? - Schnapp, Benjamin H. (West J Emerg Med, 2020)
INTRODUCTION: Emergency physicians encounter scenarios daily that many would consider “disgusting,” including exposure to blood, pus, and stool. Physicians in procedural specialties such as surgery and emergency medicine (EM) have lower disgust sensitivity overall, but the role this plays in clinical practice is unclear. The objective of this study was to determine whether emergency physicians with higher disgust sensitivity see fewer “disgusting” cases during training. METHODS: All EM residents at a midsize urban EM program were eligible to complete the Disgust Scale Revised (DS-R). We preidentified cases as “disgust elicitors” based on diagnoses likely to induce disgust due to physician exposure to bodily fluids, anogenital anatomy, or gross deformity. The “disgust elicitor” case percent was determined by “disgust elicitor” cases seen as the primary resident divided by the number of cases seen thus far in residency. We calculated Pearson’s r, t-tests and descriptive statistics on resident and population DS-R scores and “disgust elicitor” cases per month. RESULTS: Mean DS-R for EM residents (n = 40) was 1.20 (standard deviation [SD] 1.24), significantly less than the population mean of 1.67 (SD 0.61, p<0.05). There was no correlation (r = −0.04) between “disgust elicitor” case (n = 2191) percent and DS-R scores. There was no significant difference between DS-R scores for junior residents (31.1, 95% confidence interval [CI], 26.8–35.4) and for senior residents (29.0, 95%CI, 23.4–34.6). CONCLUSION: Higher disgust sensitivity does not appear to be correlated with a lower percentage of “disgust elicitor” cases seen during EM residency.